Specificities of Formation and Realization of Migrants’ Social Rights in Russia and China - Anatoly Vladimirovich Kluev; Syaobo Mou (Управленческое консультирование)
In this article are shown migration processes, which are happening in Russia and China. A special attention is given to legislative framework, on which is based migration pressure’s regulation. There is an accent on the social support development of migrants in Russia and internal migrants in Chine. It’s shown, that specific of social and legal statuses of external and internal migrants in these countries determines different forms of social support.